Ridsdalea alba (Rubiaceae), a new species from southern Thailand - Khammongkol, Kwanjai; Chamchumroon, Voradol; Poopath, Manop; Vajrodaya, Sarunya; Sungkaew, Sarawood (Phytotaxa, 2018)
Ridsdalea alba, a new species of Gardenieae from southern Thailand, is described and illustrated. It differs from R. sootepensis in having narrowly elliptic-oblong to obovate leaf blades that are glossy dark green above, thickly leathery in texture, with rounded to acute leaf apices, and revolute leaf margins. Moreover, the corolla tube is without purple speckles inside.